2022
DOI: 10.1037/gdn0000152
|View full text |Cite
|
Sign up to set email alerts
|

Examining state and trait alliance in group therapy: A within-person and between-person actor–partner interdependence model.

Abstract: Objective: Session-to-session fluctuations in alliance (i.e., state-like alliance) have been found to predict subsequent treatment outcome, especially in treatments in which working through ruptures and repairs in alliance is conceptualized as a main mechanism of change. Despite these advancements in the alliance literature, to our knowledge, no study has directly examined the roles of the state-like and trait-like alliance in group therapy. Method: Data for this study were provided by 61 patients hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Testing the same individual in several types of interactions and relationships (e.g., romantic partner, best friend, manager, child or parent, friendly stranger, unfriendly stranger) and in different settings (e.g., face-to-face treatment vs. telepsychotherapy) can crystalize individual-specific signatures using methods like round robin (Kenny, 1994(Kenny, , 2019. Although in traditional psychotherapy settings, most patients are treated by a single therapist, other unique settings exist (Kivlighan et al, 2022). Moreover, even in traditional settings, patients tend to interact with multiple professionals who engage therapeutically with them: diagnosticians, therapists, evaluators, case managers, and others, and the different interactions can serve to crystalize the patients' trait-like tendencies (Moggia et al, 2023).…”
Section: Identifying Trait-like Signaturesmentioning
confidence: 99%
“…Testing the same individual in several types of interactions and relationships (e.g., romantic partner, best friend, manager, child or parent, friendly stranger, unfriendly stranger) and in different settings (e.g., face-to-face treatment vs. telepsychotherapy) can crystalize individual-specific signatures using methods like round robin (Kenny, 1994(Kenny, , 2019. Although in traditional psychotherapy settings, most patients are treated by a single therapist, other unique settings exist (Kivlighan et al, 2022). Moreover, even in traditional settings, patients tend to interact with multiple professionals who engage therapeutically with them: diagnosticians, therapists, evaluators, case managers, and others, and the different interactions can serve to crystalize the patients' trait-like tendencies (Moggia et al, 2023).…”
Section: Identifying Trait-like Signaturesmentioning
confidence: 99%
“…Recent methodological considerations underlined the importance of disentangling stable, traitlike differences in patients’ ability to form a strong working relationship with their therapist from statelike improvements of the alliance throughout treatment, that might reflect a mechanism of therapeutic change (Zilcha-Mano, 2017). Subsequent studies demonstrated that not only trait differences in alliances, but also statelike improvements of the alliance throughout treatment affect individual patient’s outcomes (Kivlighan et al, 2022; Zilcha-Mano, 2017; Zilcha-Mano & Fisher, 2022).…”
Section: Attachment Theorymentioning
confidence: 99%
“…What we have learned so far is that individuals who have stronger alliances with the therapist, measured by questionnaires at the end of each session, experience better outcomes if the groups' average alliance with the therapist is also strong (Kivlighan et al, 2022). From the vantage point of synchrony research, we have learned that movement synchrony in the client-therapist dyad signals better results from individual sessions and in the longer term (Ramseyer & Tschacher, 2016) so long as the therapist was leading the client and not the other way around (Ramseyer, 2020).…”
Section: Future Applicationsmentioning
confidence: 99%
“…In another example, Kivlighan et al (2022) studied self-reports of alliances with the group leader among adult psychiatric participants in two types of group therapy. They investigated the specific effects of transient (“state-like”) alliances that might be observed in particular sessions and (“trait-like”) alliances that persist across sessions.…”
Section: Approaches To Group Dynamicsmentioning
confidence: 99%